Experimental Performance Analysis Of Macrobending Loss Characteristics In Polymer Optical Fiber - Haroon, Hazura; Abu Mansor, Abdul Aziz; Abdul Razak, Hanim; Idris, Siti Khadijah; Mohd Zain, Anis Suhaila; Salehuddin, Fauziyah (Penerbit Akademia Baru, 2019)
An investigation of bending loss characteristics of a Polymer Optical Fiber is presented experimentally. Loss of optical power in an optical fiber due to bending has been investigated for a wavelength of 650 nm. Variations of bending loss with different lengths have been measured, with a number of radii of curvature. Bending Loss equations for short length POF is proposed, which shows the dependence of bending loss on the curvature radii. The equations can be an initial reference or aid in predicting the loss contributes by the polymer optical fiber.